A study on the viability of the rear seat belt law in Malaysia /Jihad Syahida Nadia Zakaria... [et al.] - Zakaria, Jihad Syahida Nadia; Saiful Azhar, Adlin Shazana; Abdul Jalil, Hafiza; Tajuddin, Izzati (2009)
This paper studies the viability of the newly implemented rear seat belt law in Malaysia. To extract relevant information, semi-structured interviews were conducted with three road traffic authorities to supplement the library-based information which were mostly on global illustrations of the rear seat belt law being implemented. Factors like safety, culture and passenger overload were considered to be largely insufficient to influence the viability of this law from being implemented. Our study also signify that although it is too soon to study whether this newly legislated law will be able to reduce the rate of fatalities in our country, worldwide statistics have proven this fact. Finally, our findings indicate that although the relevant government bodies are certain that enough research has been done to prove the suitability of the rear seat belt law in Malaysia, the end-result will largely depend on public's compliance of the law.